2007
DOI: 10.1002/ijc.22747
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of matrix metalloproteinases‐1, ‐2, ‐7 and ‐13 and tissue inhibitors of metalloproteinases‐1, ‐2, ‐3 and ‐4 in colorectal cancer

Abstract: Strong expression of many matrix metalloproteinases (MMPs) has been related to poor survival of colorectal cancer (CRC) patients. The expression of tissue inhibitors of metalloproteinases (TIMPs) has been associated with both a beneficial and a poor outcome and there is thus a need to further clarify the significance of MMPs and TIMPs in CRC. The prognostic significance of 4 MMPs and TIMPs in CRC was evaluated. Formalinfixed, paraffin-embedded tissue arrayed samples of 351 patients with primary colon or rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
91
3
4

Year Published

2008
2008
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 52 publications
16
91
3
4
Order By: Relevance
“…These results are consistent with previous reports that show stroma-restricted expression of the MMPs in human liver metastases of colorectal cancer (21,22). Abundant expression of MMP2 or MMP9 is associated with poor prognosis and high mortality of colon cancer patients (23)(24)(25)(26)(27). Although selective inhibitors of MMP2/9 significantly block mouse liver metastasis of colon cancer and prolong the survival of tumor-bearing mice (28), clinical trials for MMP inhibitors have failed because of severe side effects such as musculoskeletal pain and inflammation (29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous reports that show stroma-restricted expression of the MMPs in human liver metastases of colorectal cancer (21,22). Abundant expression of MMP2 or MMP9 is associated with poor prognosis and high mortality of colon cancer patients (23)(24)(25)(26)(27). Although selective inhibitors of MMP2/9 significantly block mouse liver metastasis of colon cancer and prolong the survival of tumor-bearing mice (28), clinical trials for MMP inhibitors have failed because of severe side effects such as musculoskeletal pain and inflammation (29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…The cutoff point analysis showed a broad range of MMP-2 levels with a significant and unidirectional relation with survival outcome: high tumour MMP-2 levels are unfavourable for the patients' prognosis. Our ELISA-derived MMP-2 data correspond very well with a recent immunohistochemical study in a group of 351 colorectal cancer patients, showing that high expression of MMP-2 in malignant epithelium as well as in the surrounding stroma was associated with reduced survival (Hilska et al, 2007). Similar analysis on our tumour MMP-9 data revealed that not only patients with the highest, but also those with the lowest levels had a worse survival than patients with intermediate levels.…”
Section: Discussionsupporting
confidence: 89%
“…The involvement of different molecular pathways in colorectal carcinogenesis is exemplified by the fact that cancers of "mutator" phenotypes preferentially occur in the proximal (right side) colon, whereas the adenomacarcinoma sequence phenotype is characteristic of carcinomas in the distal (left side) colon and rectum [22,23] . Corresponding differences have also been shown in association with other potential prognosticators [24] . Interestingly, a marginally significant relation was observed between the NI and MI and response to treatment.…”
Section: Discussionmentioning
confidence: 53%